Dasar-Dasar Perencanaan Interior Museum - Anak Agung Ayu Wulandari (Humaniora, 2014)
Old, haunted, dark and poorly maintained are the impressions of Indonesian museums. Unlike foreign museums which are always crowded with visitors, Indonesian museums are always quiet and deserted. The biggest challenge for museums today is recognise that museums are for people and that their future depends on developing themselves to meet the needs of the people. Thus, Indonesian museums need to develop and apply mass communication model combined with the interpersonal communication model where in this type of communication visitors are allowed to participate in the exhibition and become part of the exhibition since this is what nowadays visitors desired to do. With a better planned exhibition interior design, following the basic design principles such as transforming space with harmony, creating room atmosfer, pacing and circulation, suitable lighting design and display as well as using appropriate presetantion technique combined with technology and multimedia, an exhibition will become a more interactive and attractive that will meet visitor’s expectation